Association of the genetic polymorphisms in pre-microRNAs with risk of childhood epilepsy in a Chinese population. (August 2016) - Li, Yang; Wang, Jinqiu; Jiang, Chunming; Zheng, Guo; Lu, Xiaopeng; Guo, Hu
Highlights: The selected four SNPs in pre-microRNAs were not associated with childhood epilepsy risk. The G allele of rs57095329 could increase drug-resistance risk of childhood epilepsy. Rs57095329 polymorphism was associated with seizure severity in childhood epilepsy. Abstract: Purpose: MicroRNA (miRNA), functions as gene regulators, plays crucial roles in pathogenesis of epilepsy. We hypothesized that single nucleotide polymorphisms (SNPs) in miRNA may be associated with childhood epilepsy. Method: We first genotyped the selected four SNPs (miR-146a rs57095329, miR-149 rs2292832, miR-196a2 rs11614913, and miR-499 rs3746444) in 267 paired childhood epilepsy patients and controls using the TaqMan assay, and evaluated the associations of the four SNPs with the risk of epilepsy. In addition, we evaluated the associations of these SNPs with drug-resistance in 95 drug-resistant and 172 drug-responsive epilepsy patients. Furthermore, the genotype-phenotype correlation was assessed in 95 drug-resistant epilepsy patients. Results: The selected four SNPs (miR-146a rs57095329, miR-149 rs2292832, miR-196a2 rs11614913, and miR-499 rs3746444) were not significantly different between epilepsy patients and controls ( P  > 0.05 for all). However, the miR-146a rs57095329 A/G genotypes were significantly associated with increased drug-resistance risk of epilepsy patients in allelic comparison (OR = 2.363, 95%CI = 1.608–3.472, P  < 0.001), heterozygote model (OR = 2.341, 95%CI = 1.301–4.211, P  = 0.005), homozygote model (OR = 1.791, 95%CI = 1.239–2.589, P  = 0.002), dominant model (OR = 2.625, 95%CI = 1.558–4.425, P  < 0.001), and recessive model (OR = 2.336, 95%CI = 1.166–4.673, P  = 0.017). Moreover, subjects with the rs57095329 GG genotype had significantly higher NHS3 score than subjects with AA genotype ( P  < 0.001) and AG genotype ( P  = 0.013) in the drug resistant patients. Conclusion: miR-146a rs57095329 polymorphism might be involved in the genetic susceptibility to drug-resistance and seizure severity in childhood epilepsy patients.